Ectopic pregnancy in a Caesarean section scar: a case study - Piotr Niziurski; Rafał Rudziński; Olga Adamczyk-Gruszka; Jakub Gruszka (Studia Medyczne, 2013)
Implantation of a pregnancy in a scar after Caesarean section is one of the rarest locations of ectopic pregnancies. A diagnosis and/or treatment which is too late may lead to a uterine rupture, the necessity to remove the uterus and a significant increase in morbidity among mothers. The study presents a diagnostically difficult case of a 29-year-old woman, who was diagnosed with pregnancy in its seventh week, located in a scar after a Caesarean section, with highly increased values of human chorionic gonadotropin (β-HCG) concentration in blood serum. The pregnancy was removed and the wound was stitched during laparotomy, without a need to remove the uterus.